2018
DOI: 10.1038/s41419-018-0562-5
|View full text |Cite
|
Sign up to set email alerts
|

CCL4 enhances preosteoclast migration and its receptor CCR5 downregulation by RANKL promotes osteoclastogenesis

Abstract: Chemokine CCL4 (MIP-1β) is released from osteoblast cells to restore the homeostasis of hematopoietic stem cells during the activation of bone marrow. In this study, we investigated the function of CCL4 and its receptor CCR5 during osteoclastogenesis. CCL4 promoted the migration and viability of preosteoclast cells. However, CCL4 had no direct effect on the receptor activator of nuclear factor-κB ligand (RANKL)-induced osteoclast differentiation in mouse preosteoclast cells. In addition, CCR5 expression was ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 49 publications
2
16
0
Order By: Relevance
“…Competitive transplantation studies with HSCs with either CCL5 -deficient or CCL5 -replete cells did not demonstrate differences in the levels of total engraftment (Ergen et al., 2012). Since ligands for CCR5 include CCL3 and CCL4, it is possible that these ligands could provide functional redundancy for CCR5 signaling when CCL5 alone is depleted (Lee et al., 2018, Menten et al., 2002). For these reasons, we sought to genetically abolish CCR5 signaling by using Ccr5 -deficient mice.…”
Section: Discussionmentioning
confidence: 99%
“…Competitive transplantation studies with HSCs with either CCL5 -deficient or CCL5 -replete cells did not demonstrate differences in the levels of total engraftment (Ergen et al., 2012). Since ligands for CCR5 include CCL3 and CCL4, it is possible that these ligands could provide functional redundancy for CCR5 signaling when CCL5 alone is depleted (Lee et al., 2018, Menten et al., 2002). For these reasons, we sought to genetically abolish CCR5 signaling by using Ccr5 -deficient mice.…”
Section: Discussionmentioning
confidence: 99%
“…In line with this observation, another study reported that treatment of mouse osteoclast progenitor cells with CCL4 did not influence RANKL-mediated osteoclastogenesis. However, the decrease in expression of its receptor CCR5 during osteoclast formation, was shown to be essential for osteoclastogenesis (106).…”
Section: Influence Of Cc-chemokines On Bone Remodeling In Health and mentioning
confidence: 99%
“…In contrast to MCP-1, which fully reversed GM-CSF repression of osteoclast formation, RANTES recovered multinuclear cell formation, but the cells lacked the ability to resorb bone [27••]. Consistent with the expression of its receptor, and another potential receptor of MCP-1, CCR4 in human osteoclast precursors [35], CCL4 (also known as MIP1b) does not enhance osteoclast formation but was found to be chemotactic to osteoclast precursors [37]. Therefore, several chemokines of the CC family (MCP-1, CCL3 and CCL5) are produced in differentiating human osteoclasts and all have similar actions in promoting osteoclast fusion and survival.…”
Section: The Role Of Mcp-1 In Bone Remodellingmentioning
confidence: 95%